Cerebral Protection Device Deployment Via Left Radial Artery During TAVI in Presence of Truncus Bicaroticus - Angshuman Maulik, MD; Kenneth Morgan, PhD; Muhammad Aetesam-ur-Rahaman, MBBS; Ian Hall, MD; Javaid Iqbal, PhD (JACC: Case Reports, 2023)
Patients with anomalous aortic arch undergoing transcatheter aortic valve implantation may require modifications to the deployment protocols of cerebral protection device systems. We share the first reported case, to our knowledge, of a cerebral protection device via the left radial artery and using a distal basket alone in a patient with truncus bicaroticus and arteria lusoria. (Level of Difficulty: Intermediate.)